(untitled) (Teología, 2020)
The article addresses the subject of death as departure from the standpoint of the spiritual process that takes place in such circumstances. Using a biographical testimony, the author examines the experience from the conceptualization of the subject made by an American author (J. Rupp) in her book Praying our goodbyes and draws some conclusions about this process.